O compliance e os sistemas preventivos anticorrupção na atividade empresarial - Gouvêa, Claudiane Rosa (2020)
Interesting to remember, with economic globalization and the influence of technological development, transnational companies emerged, culminating in an increase in economic relations between countries, but when analyzing the existing relationship, the company's image and organizational principles, it is also conducive to facing corrupt practices. Because of this, the present study begins based on the reasons that support the elaboration of compliance programs, when issues related to preventive anti-corruption systems are demanded, imposing on companies the need to take precautions through the construction and constitution of the organizational code of conduct as a guarantee of such relevance of its values. In this trajectory, are analyzed the variety and multiplicity of the norms of guidelines on disciplinary measures, preceded by a code that signals controls, rules and problem prevention, implying in the management and reduction of risks in favor of corporate goodness and integrity. In this way, it is important to verify the preventive function of combating corporate wrongdoing that the institute of criminal compliance exercises, aiming not only to ensure fulfillment of legislation but also to eradicate companies that have the greatest impact. If analyzed, however, Law 12.846 / 13 - Anticorruption Law or clean company law, in its text it is necessary to verify the objective responsibility of the juridical person, being certain that criteria of favoring or discriminating people will not be used for the investigation of fraud or illegal acts when actively performed by corporate governance. Linked to all this, it is proposed to reflect, as a company is centered on the culture of compliance, it is not a guarantee of preservation of its corporate integrity because due to free competition, the possibility of relating to a company that develops criminal practices arises.